The Effect of Reducing Vibration Of Lathe to Aisi 4340 Surface Roughness - Yudhistira, Gilang Awan; Fitri, Muhamad; Mizan, Adlan; Rafi, Muhammad Miftah; Anugrah, Hasan (Universitas Mercu Buana, 2023)
One of the quality affected factors of machined products is surface roughness, which is affected by several factors, like force and vibration. Vibration is the derivation of deflection. To improve efficiency of double chuck, in this experiment will modify the holder of double chuck to decrease the vibration. The modifications are divided into used wood to decrease length force from clamp and change the entry angle from 45° to 90°. The vibration was measured by a vibrometer at the vertical axis. Each modification succeeded to decrease the vibration at a reduction of 1.5 mm, where the highest decrease was changed the entry angle from 0.21-0.23 m/s2 to 0.10 m/s2. Modification on changed the entry angle has better surface roughness which the value of 1.3 µm.